Pemodelan DSS - Edy Supriyanto (Universitas Stikubank, 2002)
The passage analize about the model of DSS. Models begins step from DSS concept. After that, we must choose modeling approach, beside decision making processes. We have many types of model DSS, especially in statistical, financial and optimization. Finally, we get benefit of models.